2015
DOI: 10.1016/j.jtos.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eyelid Warming Devices on Tear Film Parameters in Normal Subjects and Patients with Meibomian Gland Dysfunction

Abstract: Our results suggest that repeated eyelid warming with a non-wet device improves tear film function in normal individuals and may have beneficial effects on both tear film and meibomian gland function in MGD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 43 publications
2
82
1
Order By: Relevance
“…Several studies [68] have reported the improvement in meibomian gland secretion after one 12-minute treatment by LipiFlow and the effects last up to one year. Tear film breakup time (TBUT) and symptom scores also showed improvement compared with traditional therapies [911].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [68] have reported the improvement in meibomian gland secretion after one 12-minute treatment by LipiFlow and the effects last up to one year. Tear film breakup time (TBUT) and symptom scores also showed improvement compared with traditional therapies [911].…”
Section: Introductionmentioning
confidence: 99%
“…Various treatment options for MGD including the LipiFlow instrument, intense pulsed light, eyelid-warming devices, intraductal probing, as well as topical or oral application of drugs have been developed [11][12][13][14][15][16][17][18][19]. Our present results regarding additional instruction by nurses for improving the outcome of treatment with the Azuki-no-chikara eyelid-warming device may also be applicable to other treatment approaches.…”
Section: Resultsmentioning
confidence: 97%
“…We have previously reported that eyelid warming with Azuki-no-chikara improved tear film parameters in a different hospital [11]. Previous study basically included severe MGD patients thus the clinical parameters may be improved, thus it may not be adequate to compare these studies.…”
Section: Control Group Additional Instruction Groupmentioning
confidence: 99%
“…Significant difference was found in sex between the two groups(P<0.01). MGD was diagnosed by the following evidence as previously reported[13]: 1) presence of ocular symptoms; 2) at least one lid margin abnormality including irregular lid margin, vascular engorgement, plugged meibomian gland orifices and anterior or posterior displacement of the mucocutaneous junction and 3) impaired meibum expression. Ocular symptom was determined by Ocular Surface Disease Index (OSDI), and the subject with score of > 12 was considered abnormal[14].…”
Section: Methodsmentioning
confidence: 99%